The Impact of EU Funds on the Development of a Business Model for Small and Medium-Sized Enterprises - Oliński, Marian; Szamrowski, Piotr (Olsztyn Economic Journal, 2016)
The increased interest in business models can be observed in the second half of the 90s of the last century. The research objective of this study is to assess the impact of grants received by companies on the formation of the business model. The study used the "Canvas" model proposed by A. Osterwalder and Y. Pigneur and covered micro, small and medium-sized enterprises based in rural areas, which received support in the form of investment grants under the Regional Operational Programmes between 2007-2013 for northern Poland. The results indicate that investment grants clearly influenced the modification of the business model elements, which are located on the left side of the "Canvas" template.